Performance and fouling characteristics of direct contact membrane distillation applied to raw and membrane bioreactor-treated landfill leachate - Samunya Sanguanpak; Pawinee Milintawisamai; Wilai Chiemchaisri; Chart Chiemchaisri (Case Studies in Chemical and Environmental Engineering)
Direct contact membrane distillation (DCMD) was applied to the treatment of raw and membrane bioreactor (MBR)-treated municipal landfill leachate. The experiments were conducted using feed side temperatures of 50, 60, and 70oC while permeate side temperature was controlled at 10oC. The effects of organic matter, solid particles, and salinity presented in raw leachate and MBR permeate on the DCMD flux and pollutant rejection efficiencies were investigated. Moreover, fouling and wetting of the MD membrane were examined. The experimental results revealed that the application of DCMD to MBR permeate yielded higher fluxes than those of raw leachate but its higher flux decline was also observed due to the formation of denser foulant layer on the MD membrane surface. High organic carbon and salt rejection efficiencies (>90 %) were achieved and maintained in DCMD treating MBR permeate. Significant deterioration of organic rejection efficiencies was observed in DCMD treating raw leachate at higher feed temperature (70oC) and increasing pollutant concentrations during closed-loop operation. Partial volatilization of volatile fatty acids from the feed side and their penetration through MD was also observed, being more severe at higher feed temperatures. The best condition for the operation of the system was found at 50oC using MBR permeate as feed water at which pollutant rejection efficiencies were highest while membrane wetting and fouling were also minimized.